Effects of disputes and easement violations on the cost-effectiveness of land conservation - Richard Schuster; Peter Arcese (PeerJ, 2015)
Conservation initiatives to protect and restore valued species communities in human-dominated landscapes face challenges linked to their potential costs. Conservation easements on private land may represent a cost-effective alternative to land purchase, but long-term costs to monitor and enforce easements, or defend legal challenges, remain uncertain. We explored the cost-effectiveness of conservation easements, defined here as the fraction of the high-biodiversity landscape potentially protected via investment in easements versus land purchase. We show that easement violation and dispute rates substantially affect the estimated long-term cost-effectiveness of an easement versus land purchase strategy. Our results suggest that conservation easements can outperform land purchase as a strategy to protect biodiversity as long as the rate of disputes and legal challenges is low, pointing to a critical need for monitoring data to reduce costs and maximize the value of conservation investments.